An Asymmetric Investigation of the Nexus Between Economic Policy Uncertainty, Knowledge Spillover, Climate Change, and Green Economy: Evidence From BRIC Nations - Liang, Zizheng; Qamruzzaman, Md. (Frontiers in Environmental Science, 2022)
The object of the study to gauge the impact of economic policy uncertainty (EPU), knowledge spillover (KS), and climate change (CC) on green economy (GE) transition in BRIC nation for the period from 1991-2018. The study applied several unit root tests, including DF-GLS and Zivot–Andrew, for ascertaining the stationarity properties of variables. The long-run association between variables was detected by employing ARDL bound test, tBDM test, and Bayer and Hanck combined cointegration test. Furthermore, the asymmetric effects of EPU, KS, CC on GE were examined by implementing nonlinear ARDL (NARDL) and finally, directional causal effects evaluated with the Toda-Yamamoto causality test. In addition, the long-run coefficient's robustness was assessed by applying Fully-modified OLS, Dynamic OLS and Canonical Cointegrating Regression (CCR). ARDL bound testing confirms the long-run association in the empirical model for all countries with negative statistically significant effects from EPU and CC to the green economy and positive statistically significant impacts from KS to GE. On the other hand, asymmetric assessment established both long-run and short-run asymmetry between EPU, KS, CC, and GE. Finally, directional causality establishes feedback hypothesis holds for EPU and GE in Brazil, India, China, KS, and GE in Brazil, Russia, and China. Thus, study findings establish that the transition to the green economy in BRIC nations might influence EPU and KS. Thus, for policy formulation targeted to green economic development, it is imperative to put extra effort into understanding the role of EPU and knowledge spillover in the economy.